Public’s awareness and attitude towards counterfeit medicines in Sudan: A cross-sectional study - Wala Wagiealla Wagiealla, Shaza Wagiealla Shantier, Elrasheed Ahmed Gadkariem (Journal of Applied Pharmaceutical Science, 2022)
The aim of the present study was to assess the awareness and attitude of the public in Sudan toward counterfeit medicines (CFMs). A cross-sectional study was conducted applying a pretested and structured questionnaire. The awareness and attitude were assessed statistically, and the association between those and different demographic characteristics was calculated using Fisher’s exact test and Spearman’s correlation test. A total of 386 participants enrolled in the study. The majority of the respondents (58%) were found to be aware of the term CFMs with social media mentioned to be the main source. More than half of the respondents (73%) considered CFMs of worse quality suggesting getting the medicine from a trustworthy pharmacist in order to avoid buying CFMs. The ability to distinguish CFMs from the side effects rather than the package and cost was reported by 56% of the respondents. 68% of the participants were found to have a fair awareness of CFMs. Furthermore, 80% of them showed a good attitude toward CFMs. The findings of the study reflect that attention and concentrated efforts are required on the part of the government, drug manufacturers, and healthcare providers’, especially pharmacists, to ensure that only drugs of acceptable quality reach the patient.
Keywords: Counterfeit medicines, public awareness, attitude, statistical analysis, healthcare providers